Important Parameters for Hand Function Assessment of Stroke Patients - H. Abdul Rahman; C. F. Yeong; K. X. Khor; E. L.M. Su (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
Clinical scales such as Fugl-Meyer Assessment and Motor Assessment Scale are widely used to evaluate stroke patient's motor performance. However, the scoring systems of these assessments provide only rough estimation, making it difficult to objectively quantify impairment and disability or even rehabilitation progress throughout their rehabilitation period. In contrast, robot-based assessments are objective, repeatable, and could potentially reduce the assessment time. However, robot-based assessment scales are not as well established as conventional assessment scale and the correlation to conventional assessment scale is unclear. This paper discusses the important parameters in order to assess the hand function of stroke patients. This knowledge will provide a contribution to the development of a new robot-based assessment device effectively by including the important parameters in the device. The important parameters were included in development of iRest and yielded promising results that illustrate the potential of the important parameters in assessing the hand function of stroke patients.